Faktor yang Berhubungan dengan Kejadian Hipertensi Usia Produktif di Wilayah Kerja Puskesmas Tamalanrea Jaya Makassar - Firman; Ridwan Amiruddin; Indra Dwinata (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Hypertension or high blood pressure is a condition with blood pressure constantly increasing in blood vessels. WHO defines hypertension as systolic blood pressure ≥ 140 millimeters of mercury (mmHg) and / or diastolic blood pressure ≥ 90 mmHg. Hypertension contributes 7% of the world disease burden and causes 17 million deaths annually. The prevalence of hypertension (age ≥ 18 years) in the world is 22%. In Southeast Asia, the prevalence of hypertension is 24.7% with the rate based on gender higher in men at 25.3% and in women 24.2%. This study aims to determine factors associated with the incidence of Productive age hypertension in the working area of ​​Tamalanrea Jaya Health Center in 2019. The type of research used was observational analytic with cross sectional study design. The population in this study were all sufferers of productive age hypertension (15-64) years recorded in the Tamalanrea Jaya Health Center register book in the span of time starting in January to September 2019 in the amount of 215 people. The sampling technique used was simple random sampling with a sample size of 140 patients. From the research, it was found that from the total respondents there were 42.1% included in the category of controlled hypertension and 57.9% uncontrolled hypertension. Statistical test results showed that medication adherence (p = 0.002), sodium / salt consumption (p = 0,000), BMI (p = 0.571), and stress level (p = 0.755). This study it can be seen that there is a relationship between medication adherence and sodium / salt consumption to the incidence of hypertension. A set of BMI and stress level shows that there is no relationship between BMI and the incidence of hypertension.